Critical thinking : - Chatfield, Tom (Sage Publications Ltd, 2018)
"This helpful book is your personal toolkit for critical thinking. Author Tom Chatfield will show you how to sharpen your critical thinking by developing and practicing this specific set of skills, so you can: Spot an argument and understand why reasoning matters; Discover errors and evaluate evidence; Understand and account for bias; Become a savvy user of technology; and Develop clear, confident critical writing